2021
DOI: 10.1097/md.0000000000027604
|View full text |Cite
|
Sign up to set email alerts
|

Association between SOCS3 hypermethylation and HBV-related hepatocellular carcinoma and effect of sex and age

Abstract: Background: Suppressor 3 of cytokine signaling (SOCS3) hypermethylation has been reported to participate in hepatocellular carcinoma (HCC) development and progression, but conflicting results were published. This study aimed to analyze the clinical effects of SOCS3 hypermethylation in HCC and the effects of sex and age on SOCS3 hypermethylation in HCC.Methods: Databases were searched for relevant case-control and cohort studies on SOCS3 hypermethylation in HBV-related HCC. In vitro and in vivo studies and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The physiological processes by which long-term inflammatory reactions in the colon may encourage CRC remain unclear; they may involve the decreased negative control of IL-6 signaling toward STAT3 activations through the loss of SOCS3 expression, releasing the full toxic potential of this transcription factor ( 61 ). It has also been discovered that hepatocellular carcinoma (HCC) linked to the hepatitis B virus is associated with SOCS3 hypermethylation ( 91 ).…”
Section: Roles Of Dnam In Ibdmentioning
confidence: 99%
“…The physiological processes by which long-term inflammatory reactions in the colon may encourage CRC remain unclear; they may involve the decreased negative control of IL-6 signaling toward STAT3 activations through the loss of SOCS3 expression, releasing the full toxic potential of this transcription factor ( 61 ). It has also been discovered that hepatocellular carcinoma (HCC) linked to the hepatitis B virus is associated with SOCS3 hypermethylation ( 91 ).…”
Section: Roles Of Dnam In Ibdmentioning
confidence: 99%
“…The leptin signaling cascade can be involved in changes in susceptibility to cancer processes and it has been suggested that genetic variations in JAK2 are involved in the generation of several signs of myeloproliferative neoplasms [ 227 ], as well as SOCS3 polymorphisms, that may favor the progression towards liver fibrosis and hepatocellular carcinoma [ 228 ]. Hypermethylation of SOCS3 has been reported to contribute to hepatocellular carcinoma development and progression [ 229 ].…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…It is proposed that the reduced expression of SOCS3 results in sustained activation of the IL-6/STAT3 pathway, which could be essential to hepatocarcinogenesis [ 91 ]. Similarly, a recent meta-analysis work demonstrated that the SOCS3 hypermethylation is associated with HBV-related HCC [ 92 ], and this may validate the possibility of SOCS3 expression or methylation status of the SOCS3 gene as a prognosis marker for HCC associated with HBV infection [ 93 ].…”
Section: Liver Regeneration and Hccmentioning
confidence: 99%